Effect of troxerutin on the expression of genes regulating mitochondrial biogenesis and microRNA-140 in doxorubicin-induced testicular toxicity - Behnaz Mokhtari; Arezou Abdi; Seyed Zanyar Athari; Hojjatollah Nozad-Charoudeh; Alireza Alihemmati; Reza Badalzadeh (Journal of Research in Medical Sciences, 2023)
Background: Application of doxorubicin (DOX) in cancer patients is limited due to its dose-dependent toxicity to nontarget tissues such as testis and subsequent infertility. Due to limitation of our knowledge about the mechanisms of DOX toxicity in the reproductive system, reduction of DOX-induced testicular toxicity remains an actual and primary clinical challenge. Considering the potentials of troxerutin (TXR) in generating a protective phenotype in many tissues, we aimed to examine the effect of TXR on DOX-induced testicular toxicity by evaluating the histological changes and the expression of mitochondrial biogenesis genes and microRNA-140 (miR-140). Materials and Methods: Twenty-four adult male Wistar rats (250–300 g) were divided in groups with/without DOX and/or TXR. DOX was injected intraperitoneally at 6 consecutive doses over 12 days (cumulative dose: 12 mg/kg). TXR (150 mg/kg/day; orally) was administered for 4 weeks before DOX challenge. One week after the last injection of DOX, testicular histopathological changes, spermatogenesis activity, and expression of mitochondrial biogenesis genes and miR-140 were determined. Results: DOX challenge significantly increased testicular histopathological changes, decreased testicular expression profiles of sirtuin 1 (SIRT-1) and nuclear respiratory factor-2 (NRF-2), and increased expression of miR-140 (P < 0.05 to P < 0.01). Pretreatment of DOX-received rats with TXR significantly reversed testicular histopathological changes, spermatogenesis activity index, and the expression levels of SIRT-1, peroxisome proliferator-activated receptor-γ coactivator 1-alpha (PGC-1α), NRF-2, and miR-140 (P < 0.05 to P < 0.01). Conclusion: Reduction of DOX-induced testicular toxicity following TXR pretreatment was associated with upregulation of SIRT-1/PGC-1α/NRF-2 profiles and better regulation of miR-140 expression. It seems that improving microRNA-mitochondrial biogenesis network can play a role in the beneficial effect of TXR on DOX-induced testicular toxicity.